STUDENTS’ PERCEPTION IN UTILIZING YOUTUBE VIDEO AS LEARNING MEDIA IN TEACHING STRESS PRONOUNCIATION - Maspufah; Afriyeni, Yeni; Zuriati, Diana; Masbiran, Gunaldi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Stressing is one of the most important pronunciation points in English conversation. Without correct stress, other people might difficult to understand what the speakers’ saying. However, the teachers as well as lecturers as the role model sometimes made inaccurate stressing which made the teaching of pronunciation is overlook. This research aimed to find out the students’ perception in utilizing youtube video as learning media in teaching stress pronunciation. The method of the research was descriptive qualitative. The sample was taken by purposive sampling techniqe. Eighteen students from the first semester of 2022/2023 academic year from a private public college in Pekanbaru were taken as the sample. The instrument used to collect data was questionaire from google form. The data were analyzed by using three data analysis theory. After analyzing the data, it was found that utilizing youtube as learning media for students was entertaining and educational. It also provided clear and accurate stress pronunciation by native speaker. Beside that students got opportunity to practice stressing pronunciation while watching the video, and the video itself can be rewound for many times, Thus, it can be concluded that students had a positive perception in utilizing youtube video as learning media in teaching stress pronunciation.